1988
DOI: 10.1002/1097-0142(19880101)61:1<36::aid-cncr2820610108>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil-associated cardiotoxicity

Abstract: Cardiotoxicity manifested as myocardial ischemia is not generally recognized as a side effect of 5-fluorouracil. However, there have been at least 35 cases reported since 1975. In only one of these cases was a somewhat detailed evaluation done to rule out underlying coronary disease. The case reported here of 5-FU cardiotoxicity included an extensive cardiac evaluation to rule out underlying coronary disease and to assess spasm. The literature on 5-FU cardiotoxicity is also reviewed, and its possible mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 11 publications
2
42
0
4
Order By: Relevance
“…Systemic 5-FU concentrations have been measured to be 1 mM ¼ 0 . 13 mg/ml (Freeman & Costanza, 1988), which is in the range of the two lowest concentrations tested in this study and where no significant changes were observed. Thus generalized echinocytosis does probably not occur during treatment with 5-FU.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Systemic 5-FU concentrations have been measured to be 1 mM ¼ 0 . 13 mg/ml (Freeman & Costanza, 1988), which is in the range of the two lowest concentrations tested in this study and where no significant changes were observed. Thus generalized echinocytosis does probably not occur during treatment with 5-FU.…”
Section: Discussionmentioning
confidence: 65%
“…It is active against solid tumours such as cancer of the breast, gastrointestinal tract, head and neck, and in recent years the intravenous use of high doses (1000 mg/m 2 ) has been widely employed. Besides the wellknown toxic effects of 5-FU, namely myelosuppression, mucositis, diarrhoea, nausea and vomiting, unexplained cardiotoxicity has been observed (Anderson et al, 1993;Baker et al, 1986;De Forni et al, 1992;Freeman & Costanza, 1988;Misset et al, 1990;Robben et al, 1993). The incidence of cardiotoxicity ranges from 1% (Anderson et al, 1993) to 18% (Cwikiel et al, 1995) and probably depends on the dose and rate of 5-FU administration.…”
mentioning
confidence: 99%
“…Various hypotheses including ischemia secondary to coronary artery spasm, interaction of FU with the coagulation system, immunoallergic phenomena, direct toxicity of FU on the myocardium have been proposed to explain the cardiotoxicity of this drug (Freeman & Costanza, 1988;. However, the precise biochemical mechanism underlying this toxic side-effect still remains unknown even if the metabolic pathways of FU have now been largely elucidated (Heidelberger et al, 1983).…”
mentioning
confidence: 99%
“…There are some well-known adverse effects of 5-FU and cardiotoxicity is one of them. Reported cardiovascular events include chest pain, dyspnea, confusion, ECG changes, vasospastic myocardial ischemia, myocardial infarction, and sudden death [1]. In terms of 5-FU induced cardiovascular toxicities, the incidence and mortality varies depending on the study.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous 5-FU infusion and/or combination therapy with cisplatin is associated with a higher incidence of cardiotoxicity [7]. Leucovorin plus continuous 5-FU infusion also increases the rate of cardiotoxicity compared with 5-FU alone [1]. Pharmacokinetics of 5-FU can be an important factor to the cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%